Biografi Syaikh Zarnuji Penulis Kitab Talim Wa Mutaallim - Ahmad Rifa'i (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2022)
The Book of Ta'lim al-Muta'allim is a classic book that is studied and studied in almost every Islamic educational institution, especially traditional educational institutions such as salaf boarding schools and modern huts because there are basically some concepts of al-Zarnuji education that are worthy of application. Being one of the books inherent in pesantren or formal education, it is not impossible, many readers of the book do not know about the biography of the author ta'lim al-Muta'allim. So it is necessary to reveal the identity of the author of the famous book of education. This paper, in addition to revealing the biography of al-Zarnuji as the author of the book Ta'lim al-Muta'allim, will also explain at a glance the content of the discussion in the book.